2005
DOI: 10.1111/j.1439-0523.2005.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of F2 and F3 plants introgressed with QTLs for clubroot resistance in cabbage developed by using SCAR markers

Abstract: Clubroot disease caused by Plasmodiophora brassicae is one of the major diseases of Brassica crops, often devastating to the cultivation of cruciferous crops in temperate regions. In a previous study (Moriguchi et al. 1999) identified three major quantitative trait loci (QTLs) for clubroot resistance, each in a separate linkage group, in a population derived from a cross between a clubroot-susceptible inbred cabbage line, Y2A and a resistant inbred kale line, K269. In this study, the original random amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…Mapping studies using molecular markers also revealed polygenic nature of the CR trait in B. oleracea (Landry et al 1992, Figdore et al 1993, Grandclément and Thomas 1996, Voorrips et al 1997, Moriguchi et al 1999, Rocherieux et al 2004, Nomura et al 2005. However, these studies showed the presence of a CR gene having large effect in this species.…”
Section: B Oleraceamentioning
confidence: 99%
“…Mapping studies using molecular markers also revealed polygenic nature of the CR trait in B. oleracea (Landry et al 1992, Figdore et al 1993, Grandclément and Thomas 1996, Voorrips et al 1997, Moriguchi et al 1999, Rocherieux et al 2004, Nomura et al 2005. However, these studies showed the presence of a CR gene having large effect in this species.…”
Section: B Oleraceamentioning
confidence: 99%
“…Moreover, synthetic amphidiploid Raphanobrassica, which was developed by the hybridization of Raphanus and Brassica, also have high levels of clubroot resistance (McNaughton 1973, Yoshikawa 1981. However, the CR gene(s) of radish has not been investigated in comparison with that of Brassica crops such as B. rapa (2n = 20, AA), B. oleracea (2n = 18, CC), and B. napus (Kuginuki et al 1997, Moriguchi et al 1999, Manzanares-Dauleux et al 2000, Suwabe et al 2003, 2006, Hirai et al 2004, Nomura et al 2005. Although QTL analysis was conducted previously by Kamei et al (2007), the clubroot resistance of radish has not been investigated at the chromosomal level.…”
Section: Introductionmentioning
confidence: 99%
“…In cabbage breeding programs for disease resistance, the identification of resistance sources is performed in parallel with the recovery of marketing type and the elimination of undesirable traits from the resistance source. This is particularly difficult when inter-specific crosses are made with resistance sources (Nomura et al 2005), or during the incorporation of the resistance trait into the desired morphotypes of B. oleracea (Bagget and Kean 1985). However, significant variability in resistance to clubroot was found among different cultivars of B. oleracea (Diederichsen et al 2009).…”
Section: Introductionmentioning
confidence: 99%